Shri Shatrunjay giriraj darshan in sculptures and architecture - Kanchansagarsuri (Shree Aagamoddharak granthamala ;, 1982)
History and art of Satrunjaya Hill, Jaina pilgrimage center in Gujarat; includes Sanskrit inscriptions.